A 15-year review of secondary and tertiary optic nerve sheath fenestration for idiopathic intracranial hypertension. (4th July 2018) - Anzeljc, Andrew J.; Frias, Patrick; Hayek, Brent R.; Canter Weiner, Nancy; Wojno, Ted H.; Kim, H. Joon
ABSTRACT: Purpose : Optic nerve sheath fenestration (ONSF) is a common surgical option for patients with idiopathic intracranial hypertension (IIH) with vision loss refractory to medical management. Little is known about the visual benefit of repeated ONSF. The authors aimed to assess the efficacy of secondary and tertiary ONSF in patients with IIH. Methods : A retrospective chart review was performed on all patients with repeat ONSF for IIH at Emory University from 1999 to 2016. Primary outcome measures included visual acuity, optic nerve head findings, and visual field results. Results: A total of nine eyes in seven patients (five females and two males) with repeat ONSF were identified. Two of the seven patients had repeat ONSF in both eyes, while the remaining five patients had only one eye repeated. Five of seven patients (five eyes) improved or remained stable after the secondary ONSF. Two patients (three eyes) continued to worsen despite the secondary fenestration surgery and underwent tertiary ONSF at an average of 13.2 months (SD 5.5 months) after the failed secondary ONSF. Both patients that underwent the tertiary fenestration showed improvement. Six of the patients had either improvement or stability in their clinical findings at their last documented follow-up, but one continued to worsen despite intervention. Conclusions: This study suggests that secondary and tertiary nerve sheath fenestration is a viable management option for patients with progressive vision loss from IIH. Repeat ONSFs do not appear to have increased complication or failure rates compared to prior documented studies regarding primary fenestrations.